Modern approach to basal-bolus therapy with glargine and glulisine insulin analoguesin various age groups - Natalya Nikitichna Volevodz (Endocrinology Research Centre, 2013)
DCCT (Diabetes Control and Complications Trial) study established that intensified insulin therapy in multiple daily injections (MDI) or continuous insulin infusion (CSII) regimens substantially reduce both development and progression of complications in patients with type 1 diabetes mellitus (T1DM) as compared to conventional insulin therapy. Insulin analogues possess better pharmacokinetic and pharmacodynamic characteristics than unmodified human insulin agents. These characteristics are beneficial for management of diabetes mellitus, allowing better glycemic outcomes with lower incidence of hypoglycemia.Current review discusses specifics of therapy with glargine (Lantus?) and glulisine (Apidra?) insulin analogues. Authors analyzed available to date results from corresponding clinical trials in children, adolescents and adults. Pharmacoeconomic aspects and matters of dosage of glargine and glulisine are further addressed.